Determinants of Life Insurance Consumption in India: Area to be Determined Till Now - Chawala, Sonia; Singh, Fulbag (Journal of Commerce and Trade, 2007)
Innumerable economic, demographic, socio cultural, political and other factors determine each economy’s consumption of life insurance. The Economic Environment consisting of foreign investment climate, price, inflation and interest rates income, saving and investment parameters may increase or decrease the overall demand of insurance. Similarly demographic environment consisting of education level, household structure, industrialization and urbanization, social environment, political environment of the nation also has a profound impact on the insurance consumption. In the present paper an attempt has been made to assess the impact on life insurance consumption in the light of trend of these factors. Indian insurance industry has good regulatory environment, political stability, changing demographic profile, good economic conditions in its favour.